SOSIALISASI PENGUNAAN PAHAT POTONG INSERT BAGI WORKSHOP USAHA BUBUT DI KOTA JAYAPURA - Ranteallo, Obet; Kaiwai, Ruben M.; Patabang, Djuarensi (Jurnal Abdi Insani, 2025)
The machining industry, particularly lathe workshops, plays a vital role in supporting the manufacturing and machinery repair sectors in Jayapura City. However, many small-scale workshops still rely on conventional cutting tools due to limited knowledge and access to modern tool technologies such as insert cutting tools. Insert tools offer several advantages, including ease of insert replacement, longer tool life, and more precise and efficient cutting results. This community service activity aims to enhance the knowledge and technical skills of lathe workshop operators in Jayapura City through outreach and training on the use of insert cutting tools. Many local workshops still use conventional tools, which have limitations in terms of efficiency and cutting quality. Therefore, this program is designed to introduce modern, economical, and practical insert tooling technology. The method used involves an educational-participatory approach through lectures, demonstrations, hands-on practice, and interactive discussions. The program encourages active participation to ensure that knowledge of insert tool usage can be effectively applied in workshop operations. The results of the program show a significant improvement in participants’ understanding, with an average post-test score increase of 35% compared to the pre-test. Participants also expressed strong interest in adopting insert tools for their production processes. During the hands-on session, they were able to correctly operate and replace the insert tools. The discussions were lively, indicating high enthusiasm for the topics presented. Overall, this activity has had a positive impact on enhancing the technical capacity of small and medium-sized lathe workshops in Jayapura City.